2015
DOI: 10.1016/j.toxicon.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

BbMP-1, a new metalloproteinase isolated from Bothrops brazili snake venom with in vitro antiplasmodial properties

Abstract: This study describes the biochemical and functional characterization of a new metalloproteinase named BbMP-1, isolated from Bothrops brazili venom. BbMP-1 was homogeneous on SDS-PAGE, presented molecular mass of 22,933Da and pI 6.4. The primary structure was partially elucidated with high identity with others metalloproteinases from Viperidae venoms. The enzymatic activity on azocasein was evaluated in different experimental conditions (pH, temperature). A significant reduction in enzyme activity after exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…In the murine model, Peruvian B. brazili exhibited minimum hemorrhagic dose (MHD) of 7.40 μg/ mouse), minimum dermonecrotic dose (MND) of 152.15 μg/ mouse, minimum coagulant dose against plasma (MCD-P) and fibrinogen (MCD-F) of 19.20 and 1020.0 μg/mL, respectively, and minimum defibrinogenating dose (MDD) of 7.0 μg/mouse [11]. Although described as a new Bothrops from Brazil 65 years ago [15], very few studies have been reported on the toxin arsenal of the Brazil's lancehead venom, and these were mainly focused on the pharmacological effects and possible biotechnological applications of isolated toxins [21][22][23][24][25][26][27][28][29][30][31], including acidic and basic phospholipase A 2 (PLA 2 ) molecules (myotoxic Braziliase I and II, MTX I and II, brazilitoxins II and III) [23][24][25][26]; a PI-snake venom metaloproteinase (SVMP), with in vitro antiplasmodial properties [27]; coagulant thrombin-like and pro-angiogenic snake venom serine proteinase (SVSP) [28,29]; and a hyaluronidase [30].…”
Section: Introductionmentioning
confidence: 99%
“…In the murine model, Peruvian B. brazili exhibited minimum hemorrhagic dose (MHD) of 7.40 μg/ mouse), minimum dermonecrotic dose (MND) of 152.15 μg/ mouse, minimum coagulant dose against plasma (MCD-P) and fibrinogen (MCD-F) of 19.20 and 1020.0 μg/mL, respectively, and minimum defibrinogenating dose (MDD) of 7.0 μg/mouse [11]. Although described as a new Bothrops from Brazil 65 years ago [15], very few studies have been reported on the toxin arsenal of the Brazil's lancehead venom, and these were mainly focused on the pharmacological effects and possible biotechnological applications of isolated toxins [21][22][23][24][25][26][27][28][29][30][31], including acidic and basic phospholipase A 2 (PLA 2 ) molecules (myotoxic Braziliase I and II, MTX I and II, brazilitoxins II and III) [23][24][25][26]; a PI-snake venom metaloproteinase (SVMP), with in vitro antiplasmodial properties [27]; coagulant thrombin-like and pro-angiogenic snake venom serine proteinase (SVSP) [28,29]; and a hyaluronidase [30].…”
Section: Introductionmentioning
confidence: 99%
“…A similar study on BMP-1, a new metalloproteinase isolated from Bothrops Brazili snake venom has an in vitro anti-plasmodial property against P. falciparum with an IC 50 of 3.2±2.0 mg/mL [29]. Recent literature described L-MAO isolated from Bothrops pirajai and Bothrops alternatus venoms had inhibited Escherichia coli growth.…”
Section: Resultsmentioning
confidence: 71%
“…Recent literature described L-MAO isolated from Bothrops pirajai and Bothrops alternatus venoms had inhibited Escherichia coli growth. Interestingly purified L-MAO of Australian elapid, Pseudechis australis (Australian king brown or mulga snake) also had antibacterial property [29]. Studies in this context include the effect of Crotalus viridis viridis snake venom on Trypanosoma cruzi, which shows a promising result of 76-93% reduction in the number of parasites per infected cell and a 94-97.4% reduction in the number of parasites per 100 cells after 96 h of infection [30].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of metalloproteinase inhibitors, EDTA and batimastat, on the metalloproteinase activity of jellyfish venom were measured with azocasein [ 74 ]. Briefly, 100 μL of the reaction mixture contained 10 μL of EDTA (final concentration, 31.2 μM–10000 μM) or batimastat (final concentration, 6.5 μM–209.4 μM), 10 μL of NnNV (3.16 μg/μL) and 80 μL of azocasein (5 mg/mL) resuspended in assay buffer (50 mM Tris, 100 mM NaCl, 5 mM CaCl 2 , pH 8.8).…”
Section: Methodsmentioning
confidence: 99%